In vitro microsomal metabolism of nuclear chloro substituted secondary amines and imines - (:unkn) unknown (Springer-Verlag France, 1997)
The metabolism of N-(4-chlorobenzyl)-4-chloroaniline (CBCA), N-(4-chlorobenzyl)-4-chlorobenzylamine (CBCBA), and N-(4-chlorobenzylidene)-4-chlorobenzylamine (CBDCBA) were studied in vitro using rat liver microsomal preparations. The secondary amines produced the corresponding N-oxidation products (hydroxylamines and nitrones) and dealkylation products (4-chlorobenzaldehyde and primary amines). Both secondary amines failed to produce the corresponding amides, whilst the parent imine was detected as a metabonate. CBDCBA, the intermediate imine of CBCBA metabolism, was also incubated under similar conditions. However, no oxaziridine was detected.
Keywords: Hydroxylamines; Metabolism; Nitrones; Oxaziridines; Secondary amines